Birds Communities at Mangrove of Batu Ampar, Kubu Raya District, West Kalimantan Province - Jarwadi Budi Hernowo (Institut Pertanian Bogor (IPB University), 2016)
Batu Ampar mangrove is an important bird habitat especially for birds which have relation to mangrove ecosystem in West Kalimantan. The research was conducted in February to March 2007, at mangrove Batu Ampar demo site. Sampling was done to get representative area for bird survey. The 19 transects were chosen as sampling site to collect bird data such as species and number of individual. Bird surveys were carried out using Reconnaissance method and IPA (Index Point of Abundance) count method. The length of each transect was approximately 500 m. The results showed that the bird community’s structure was dominated by insectivorous birds represented approximately 60% of total bird’s species at mangrove Batu Ampar demo site. The abundance between numbers of individual with the birds species have relation pattern like J opposite. Percentage of dominant bird species was approximately 11%, those are such as stork billed kingfisher, white-collared kingfisher, common iora, chestnuts-rumped babbler, Strip-Tit Babbler, magpie robin, ashy tailorbird, mangrove blue flycatcher, pied fantail, mangrove whistler, brown-throated sunbird and Cooper-Throated Sunbird. Vertical structure of mangrove vegetation was used by birds at mangrove Batu Ampar demo site is mainly B stratum, and it be used around 60 % birds species. Based on dendrogram analysis there were 5 cluster birds species. The mangrove bird specialists found at sampling area were mangrove blue flycatcher and cooper throated sunbird.